What Can Spatial Assessment Reveal About Flash Flood Risk and Ecosystem Carrying Capacity in Tropical Highland Environments? - Erna Juita; Dasrizal; Mohd Hairy Ibrahim; Elsa Yuniarti; Arie Zella Putra Ulni; Soni (Jurnal Penelitian Pendidikan IPA, 2025)
Flash floods are among the most destructive hydrometeorological hazards in tropical highland regions, yet their spatial risks remain poorly quantified in data-scarce environments. This study assessed flash flood risk in Solok Selatan Regency, West Sumatra (Indonesia), by integrating landform and slope classification with the Topographic Wetness Index (TWI) derived from a 30 m DEM. Historical records of 11 flood events between 2010 and 2020 were used for model validation. The analysis revealed that most of the regency is characterized by moderate flash flood risk, while high-risk zones are concentrated in steep fluvial landscapes. Validation against observed flood locations demonstrated a spatial match of 95.2%, confirming the reliability of the model. In addition, the evaluation of hydrological ecosystem service capacity indicated that over 80% of the landscape has only moderate regulatory function, limiting its ability to buffer runoff. These findings highlight the importance of integrating DEM-based hydrological indices with ecosystem assessments to support more effective disaster risk reduction and spatial planning in tropical highland environments.